Cómo interpretar los resultados del test estándar de lactato que se presentan en los atletas durante el ciclo de entrenamiento? - Alba Berdeal, A. L. (Archivos de medicina del deporte, 2014)
Standard lactate test is one of the tests currently used for physiological and biochemical control of high-performance athletes. In this test is determined the speed of displacement corresponding to a concentration of 4 mmol per liter of blood lactate (V4), as an indicator of the lactate threshold and the speed or the maximum rate of lactate production (VLaMax.), as an indicator of the maximum capacity of glycolysis. The objectives of this review article is to describe the methodology of the test and discuss the variations tend to occur more frequently in these variables, which are: - The V4 improvement and maximum lactate value after anaerobic eff ort remains unchanged. - V4 improvement and maximum lactate value decreases after anaerobic eff ort. - V4 remains unchanged or moves slightly to the left and the maximum value of lactate after anaerobic effort increases. - Improve both the V4 and the maximum lactate value. Based on the literature, are described for each of these variations the following: a) types of training that produce them, b) use of aerobic and anaerobic energy during exercise, c) lactate values and perceived exertion at maximum lactate steady state and during submaximal exercise intensity below maximum lactate steady state, d) percentages with respect to personal best athlete to achieve fi xed levels of lactate e) percentage that is recommended for continuous extensive and regenerative training with respect to the V4. It has to be concluded that with the knowledge of the methodology for the application of this test, the variations tend to presented in V4 and in the maximum rate of lactate production and the interpretation that should be given to each of these variations, the coach or sport scientist, have a valuable tool to control the energetic aerobic and anaerobic capacity of elite athletes.